Increasing Basic Quranic Literacy for Madrasah Ibtidaiyah in Indonesia During the New Normal Period - M Sofyan Alnashr (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2022)
The main guidelines for Muslims in living life are the Qur'an and Hadith. Therefore, Islamic teachings contained in the Qur'an and Hadith must be taught from an early age. For children in Madrasah Ibtidaiyah (MI), learning about the Quran begins with reading and writing activities, or what is known as basic literacy. This study seeks to explain how MI teachers and principals in the new normal era continue to improve basic Koran literacy for MI students. The research method used is a qualitative method with a descriptive approach. Data was collected through in-depth interviews and documentation with the object of research at MI Tarbiyatul Banin Pekalongan Winong Pati. The results showed that in the new normal era of the COVID-19 pandemic, MI Tarbiyatul Banin Qur'an and Hadith teacher carried out mixed learning, which was carried out online and face-to-face alternately. The efforts made by MI Tarbiyatul Banin in improving the basic literacy of the Koran are getting children to read and write through practice. This activity is also carried out in collaboration with parents to monitor children's basic Koranic literacy at home. Teachers always practice reading and writing habits, both in class with their teachers and at home with parental guidance.